I am trying to calculate the following probability

$$\mathbb{P} \big(\sum_{i=1}^{m} (A_i + S_i) \le L < \sum_{i=1}^{m+1} (A_i + S_i) \big)$$


$$A_i \sim \exp(\lambda), \quad S_i \sim \exp(\mu), \quad L \sim \exp(\lambda), \quad \textrm{and }\lambda \neq \mu \textrm{ are two integers.}$$

All $A_i, S_i, L$ are mutually independent. $m$ is an integer parameter.

For convenience, let $$\sum_{i=1}^{m} (A_i + S_i) \triangleq R_m, \quad \sum_{i=1}^{m+1} (A_i + S_i) \triangleq R_{m+1}.$$

I got the following hint for a startup:

"As $L$ is $\exp(\lambda)$ and independent of $(R_m, R_{m+1})$, taking expectation with respect to $L$ gives (also due to Fubini's theorem)" $$\mathbb{P}(R_m \le L < R_{m+1}) = \mathbb{E}(e^{-\lambda R_m} - e^{-\lambda R_{m+1}}).$$

I am confused about this step and not able to figure out where Fubini's theorem comes into play.

Question: Could you please give me more hints for the calculation of the above probability?

Background of the probability:

Consider an alternating renewal process, in which a system can be in one of two states: on or off. Whenever it is off, it takes a time $A_i \sim \text{exp}(\lambda)$ before turning on. Whenever it becomes on, it also remains on for a time $S_i \sim \text{exp}(\lambda)$.

Initially the system is off. A cycle $c_i$ consists of the $i$-th off-state and the $i$-th on-state. All $A_i$ and $S_i$ are mutually independent.

The question is: Given a time period $L \sim \text{exp}(\lambda)$, what is the probability that exactly $m$ cycles occur in $L$?


To simplify, consider only two independent random variables $L$ and $R$, then you are asking why $$P(R\leqslant L)=E(G(R)),$$ where the function $G$ is defined by $$G(x)=P(L\geqslant x).$$ Indeed, the reason is Tonelli theorem (the version of Fubini theorem for nonnegative functions) since $$P(R\leqslant L)=\iint\mathbf 1_{x\leqslant y}\,\mathrm dP_{(R,L)}(x,y).$$ By hypothesis, $R$ and $L$ are independent hence $P_{(R,L)}=P_R\otimes P_L$, in particular, $$P(R\leqslant L)=\iint\mathbf 1_{x\leqslant y}\,\mathrm dP_R(x)\mathrm dP_L(y),$$ and, by Tonelli theorem, $$P(R\leqslant L)=\int\left(\int\mathbf 1_{x\leqslant y}\,\mathrm dP_L(y)\right)\mathrm dP_R(x).$$ By definition of $P_L$, each inner parenthesis is $P(L\geqslant x)=G(x)$, hence, by definition of $P_R$, $$P(R\leqslant L)=\int G(x)\mathrm dP_R(x)=E(G(R)).$$ Likewise, $$P(R\leqslant L)=E(H(L)),\qquad H(y)=P(R\leqslant y).$$

  • $\begingroup$ Thanks for your simplified, yet general, derivations. $\endgroup$ – hengxin Nov 16 '14 at 7:41

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.